Interpersonal Trust and Knowledge Sharing : The moderating role of Leadership Support - Carmeviola Salsa Putrika; Syahrizal Syahrizal (Universitas Negeri Padang, 2021)
The purpose of this study was to analyze the effect of interpersonal trust on knowledge sharing among employees of Telkom Akses Sumatera Barat and the effect of interpersonal trust on knowledge sharing with support as a moderating variable on employees of Telkom Akses Sumatera Barat .The study population was all employee Telkom Akses Sumatera Barat, with a total of 255 employee. In this study the sampling technique used cluster proportional random sampling where the number of samples was 80 people. The analysis technique used is the Structural Equation Model (SEM) with the help of the SmartPLS 3.0. The result of study revealed the moderating effect of leadaership support between interpersonal trust and knowledge sharing relationship was found to be significant to employee Telkom Akses Sumatera Barat .